Phase 1, dose-escalation study of guadecitabine (SGI-110) in combination with pembrolizumab in patients with solid tumors. Issue 6 (18th June 2022) - Papadatos-Pastos, Dionysis; Yuan, Wei; Pal, Abhijit; Crespo, Mateus; Ferreira, Ana; Gurel, Bora; Prout, Toby; Ameratunga, Malaka; Chénard-Poirier, Maxime; Curcean, Andra; Bertan, Claudia; Baker, Chloe; et al.
Abstract : Background: Data suggest that immunomodulation induced by DNA hypomethylating agents can sensitize tumors to immune checkpoint inhibitors. We conducted a phase 1 dose-escalation trial (NCT02998567 ) of guadecitabine and pembrolizumab in patients with advanced solid tumors. We hypothesized that guadecitabine will overcome pembrolizumab resistance. Methods: Patients received guadecitabine (45 mg/m 2 or 30 mg/m 2, administered subcutaneously on days 1–4), with pembrolizumab (200 mg administered intravenously starting from cycle 2 onwards) every 3 weeks. Primary endpoints were safety, tolerability and maximum tolerated dose; secondary and exploratory endpoints included objective response rate (ORR), changes in methylome, transcriptome, immune contextures in pre-treatment and on-treatment tumor biopsies. Results: Between January 2017 and January 2020, 34 patients were enrolled. The recommended phase II dose was guadecitabine 30 mg/m 2, days 1–4, and pembrolizumab 200 mg on day 1 every 3 weeks. Two dose-limiting toxicities (neutropenia, febrile neutropenia) were reported at guadecitabine 45 mg/m 2 with none reported at guadecitabine 30 mg/m 2 . The most common treatment-related adverse events (TRAEs) were neutropenia (58.8%), fatigue (17.6%), febrile neutropenia (11.8%) and nausea (11.8%). Common, grade 3+ TRAEs were neutropaenia (38.2%) and febrile neutropaenia (11.8%). There were no treatment-related deaths. Overall, 30 patients were evaluable for antitumor activity; ORR was 7% with 37% achieving disease control (progression-free survival) for ≥24 weeks. Of 12 evaluable patients with non-small cell lung cancer, 10 had been previously treated with immune checkpoint inhibitors with 5 (42%) having disease control ≥24 weeks (clinical benefit). Reduction in LINE - 1 DNA methylation following treatment in blood (peripheral blood mononuclear cells) and tissue samples was demonstrated and methylation at transcriptional start site and 5' untranslated region gene regions showed enriched negative correlation with gene expression. Increases in intra-tumoural effector T-cells were seen in some responding patients. Patients having clinical benefit had high baseline inflammatory signature on RNAseq analyses. Conclusions: Guadecitabine in combination with pembrolizumab is tolerable with biological and anticancer activity. Reversal of previous resistance to immune checkpoint inhibitors is demonstrated.